Innovation effects in the IPO market : a Singapore perspective. - Lee, Ching Wei. (2012)
This paper examines the relationship between firm innovation and Initial Public Offering (IPO) performance. Existing research suggests little consensus on the relationship between innovation and the performance of IPO firms. We use signalling theory to examine how the number of patents affects the IPO performance through underpricing. Using the multiple linear regression technique on Singapore IPOs from 1994 to 2006, we found a statistically significant relationship that firms with a higher number of patents filed prior to IPO will experience a lower level of underpricing. Practical implications of these findings and future research directions are then provided.